2021
DOI: 10.1155/2021/5690868
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Multimodal Sensor Motion Intention Recognition Based on Three‐Dimensional Convolutional Neural Network Algorithm

Abstract: With the development of microelectronic technology and computer systems, the research of motion intention recognition based on multimodal sensors has attracted the attention of the academic community. Deep learning and other nonlinear neural network models have a wide range of applications in big data sets. We propose a motion intention recognition algorithm based on multimodal long-term and short-term spatiotemporal feature fusion. We divide the target data into multiple segments and use a three-dimensional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The guiding position of the Marxist College has been established, and the secretary of the Party Branch of the Marxist College is appointed by the school's party committee standing member, party committee propaganda department head, and party committee, minister of the United Front Work Department concurrently. The Party Committee Propaganda Department is the organizational department of the school's ideological education management and theoretical study [ 21 ].…”
Section: Experiments On the Curriculum Establish Of Ideological And P...mentioning
confidence: 99%
“…The guiding position of the Marxist College has been established, and the secretary of the Party Branch of the Marxist College is appointed by the school's party committee standing member, party committee propaganda department head, and party committee, minister of the United Front Work Department concurrently. The Party Committee Propaganda Department is the organizational department of the school's ideological education management and theoretical study [ 21 ].…”
Section: Experiments On the Curriculum Establish Of Ideological And P...mentioning
confidence: 99%
“…In Wen and Wang (2021) , a lower-limb motion intention recognition algorithm is proposed that utilizes multimodal long-term and short-term spatiotemporal feature fusion for accurate recognition. The input used for the algorithm is sEMG data, and the proposed algorithm consists of a 3D CNN for extracting short term spatiotemporal features in segments, Le Net and shape context to extract features of the target motion trajectory, and an LSTM network for time-series modeling of the extracted features.…”
Section: Resultsmentioning
confidence: 99%
“…The second most commonly used sensors are IMUs and sEMG sensors. IMUs are often found in exoskeleton designs and commercialized armbands, such as the Myo armband ( Ren et al, 2018 ; Cote-Allard et al, 2019 ; Su et al, 2019 ; Gardner et al, 2020 ; Viekash et al, 2021 ; Wang, 2021 ), while sEMG sensors are mainly used to measure upper-limb movements with armbands ( Cote-Allard et al, 2019 ; Young et al, 2019 ; Chen et al, 2020a ; Chen et al, 2020b ) and lower-limb movements with sEMG electrodes ( Kilic and Dogan, 2017 ; Kopke et al, 2020 ; Coker et al, 2021 ; Feleke et al, 2021 ; Viekash et al, 2021 ; Wen and Wang, 2021 ). IMUs, which measure body acceleration and angular rate, offer the advantage of being unobtrusive, portable, and relatively easy to use, making them ideal for real-time, dynamic motion tracking.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%